6(x+3)-2x=4(x+1)+14

Simple and best practice solution for 6(x+3)-2x=4(x+1)+14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(x+3)-2x=4(x+1)+14 equation:


Simplifying
6(x + 3) + -2x = 4(x + 1) + 14

Reorder the terms:
6(3 + x) + -2x = 4(x + 1) + 14
(3 * 6 + x * 6) + -2x = 4(x + 1) + 14
(18 + 6x) + -2x = 4(x + 1) + 14

Combine like terms: 6x + -2x = 4x
18 + 4x = 4(x + 1) + 14

Reorder the terms:
18 + 4x = 4(1 + x) + 14
18 + 4x = (1 * 4 + x * 4) + 14
18 + 4x = (4 + 4x) + 14

Reorder the terms:
18 + 4x = 4 + 14 + 4x

Combine like terms: 4 + 14 = 18
18 + 4x = 18 + 4x

Add '-18' to each side of the equation.
18 + -18 + 4x = 18 + -18 + 4x

Combine like terms: 18 + -18 = 0
0 + 4x = 18 + -18 + 4x
4x = 18 + -18 + 4x

Combine like terms: 18 + -18 = 0
4x = 0 + 4x
4x = 4x

Add '-4x' to each side of the equation.
4x + -4x = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 4x + -4x

Combine like terms: 4x + -4x = 0
0 = 0

Solving
0 = 0

Couldn't find a variable to solve for.

This equation is an identity, all real numbers are solutions.

See similar equations:

| 2x+10=-10+4x | | 9x-6=6+6x | | 3(2z-3)=5(z-5) | | 8(2+3z)+1=z-10(z+1) | | 12z=-72 | | 3y^4+14y^2+8=0 | | 11x-6=9+4 | | -4x+36=4(3x-3) | | 7k-10=14+3k | | 2(2z-4)=3(z-2) | | t/5=8 | | 67-4x=5x+15 | | x-1.4x+2=-3.5(x+1.2) | | 10-9x=72-23x | | (2a+3)(4a^2-6a+9)= | | 4(x+5)=5x+15 | | 4x^2=-2y^3-4y+3 | | 2x-(-20)=10 | | -4(-2k-7)=3(2k+8) | | -7y-13=-y+5 | | 12r-15s-r+3s= | | -3(1+5x)=3(-4x-2) | | 13+2(1-u)=8u-5(u+7) | | 14X=6X+16 | | 12x+48=5x-117 | | (6x-7y)(6x-7y)= | | 5x+8=-8 | | 5+(3y+3)=-(3-4)+8 | | 7m+8=3m-16 | | 6x^2=27x+15 | | 4(a+2)=2(-2+a)-4 | | 2p+18=p-8 |

Equations solver categories